Parallelising multi-agent systems for high performance computing - Leitão, Paulo (2014)
Multi-Agent Systems (MAS) are seen as a promising technology to face the current requirements of large-scale distributed and complex systems, e.g., autonomous traffic systems or risk management. The application of MAS to such large scale systems, characterised by millions of distributed nodes, imposes special demanding requirements in terms of fast computation. The paper discusses the parallelisation of MAS solutions using larger-scale distributed High End Computing platforms as well as High Performance Computing as a suitable approach to handle the complexity associated to collaborative solutions for large-scale systems.